Concordance of transient elastography and shear wave elastography for measurement of liver stiffness. Issue 4 (19th September 2017) - O'Hara, Sandra; Hodson, Susan; Hernaman, Chandelle; Wambeek, Nick; Olynyk, John
Abstract: Introduction: Transient elastography is commonly utilised in liver clinics as a non‐invasive method of assessing the degree of fibrosis or presence of cirrhosis in the human liver. Many ultrasound vendors are now providing ultrasound shear wave elastography on commercial ultrasound units. There is limited published data evaluating the performance of ultrasound elastography compared to transient elastography. Methods: This study compared the performance of ultrasound shear wave elastography, on an ultrasound unit with transient elastography in 29 participants with liver diseases of varying aetiologies. Results: The mean shear wave pressure for transient elastography and ultrasound shear wave elastography was 7.58 kPa (SD 3.26) and 7.29 (SD 2.02), respectively, with 18 cases having a less than 30% deviation of shear wave elastography from transient elastography. Conclusion: Both methods provide similar measurements of fibrosis and may be useful non‐invasive measures of hepatic fibrosis and cirrhosis.